Early-onset aggressive oesophageal carcinoma in Down’s syndrome - a coincidence or a game of extra genes? - Ashraf, Fariha; Kiran Aftab; Faisal Ibrahim; Muhammad Arsalan (Journal of the Pakistan Medical Association, 2022)
Patients with Down’s syndrome exhibit a unique pattern for a number of malignant conditions but there is inconsistent data for the risk of oesophageal cancer. We present a case of early-onset aggressive oesophageal carcinoma in a young male patient diagnosed with Trisomy21, who presented with complaints of progressive dysphagia, vomiting, voice change and weight loss. Barium swallow showed shouldering sign at distal oesophagus. GI Endoscopy revealed an irregular growth at 20cm from incisors obstructing the lumen. Histopathology confirmed well-differentiated adenocarcinoma. CT scan unmasked a circumferential mass involving the dorsal oesophagus with multiple enlarged nodes along with infiltration of basal segments of left lung staging the tumour as T3N1M0. A metallic stent was placed endoscopically through the stenotic tumour and the patient was referred for chemoradiotherapy. —Continue